Pendampingan Belajar Untuk Mengembangkan Karakter Peserta Didik Madrasah Ibtidaiyah Muhammadiyah 08 Bango Payaman Solokuro - Sari, Pusvyta; Masruri, Hadi; Rofiq, Muhammad; Zulfah, Afifatuz (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
Learning assistence activity for students of MI Muhammadiyah 08 Bango Payaman Solokuro Lamongan was carried out with the aim of providing motivation, implemented various learning methods and helping overcome learning difficulties. This activity was carried out within the framework of Kuliah Kerja Nyata of the Sunan Drajat Lamongan Islamic Boarding School Institute (KKN INSUD). Assistancing was carried out using the Participatory Action (PAR) method. The KKN INSUD group was directly involved in the learning process at the madrasah, conducting approaches and interactions with teachers and students, and providing learning guidance at the KKN post. Learning assistance and character development at the madrasah need to be continuously carried out patiently, creatively and collaboration with parents and the community. This way, students get a conducive learning environment to support more optimal self-development.